2022
DOI: 10.1016/j.bioactmat.2021.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic and anti-tumor Cu and Mn-doped borosilicate nanoparticles for syncretic bone repair and chemodynamic therapy in bone tumor treatment

Abstract: Critical bone defects caused by extensive excision of malignant bone tumor and the probability of tumor recurrence due to residual tumor cells make malignant bone tumor treatment a major clinical challenge. The present therapeutic strategy concentrates on implanting bone substitutes for defect filling but suffers from failures in both enhancing bone regeneration and inhibiting the growth of tumor cells. Herein, Cu and Mn-doped borosilicate nanoparticles (BSNs) were developed for syncretic bone repairing and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Encouraged by the effective normalization of tumor blood vessels after wireless electrical stimulation treatment, we further evaluated the anti-tumor efficacy of P-BTO nanoparticles in combination with the chemotherapy drug DOX [ 57 ]. Tumor-bearing mice were divided randomly into eight groups: blank (saline), blank + LIPUS, P-BTO, P-BTO + LIPUS, DOX, DOX + LIPUS, P-BTO + DOX, and P-BTO + DOX + LIPUS.…”
Section: Resultsmentioning
confidence: 99%
“…Encouraged by the effective normalization of tumor blood vessels after wireless electrical stimulation treatment, we further evaluated the anti-tumor efficacy of P-BTO nanoparticles in combination with the chemotherapy drug DOX [ 57 ]. Tumor-bearing mice were divided randomly into eight groups: blank (saline), blank + LIPUS, P-BTO, P-BTO + LIPUS, DOX, DOX + LIPUS, P-BTO + DOX, and P-BTO + DOX + LIPUS.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, it has been demonstrated that Cu-doped BGs and scaffolds promote endothelial cell proliferation and increase mesenchymal stem cell (MSC) differentiation levels. 118,119 To improve bone healing and anti-tumor therapy via the osteogenic properties of Cu, Libin et al 120 recently doped BBG nanoparticles with Cu. According to an in vitro study, the nanoparticle increased endothelial cell angiogenesis as well as the differentiation potential of bone marrow stromal cells (BMSCs).…”
Section: Doping Ions' Role In Regulating Bbg Degradation Rate and Ost...mentioning
confidence: 99%
“…Compared with the traditional homo-metallic CDT agents, hetero-metallic Fenton-like centers have attracted increasing attention due to their excellent conversion efficiency for hydrogen peroxide. 11–18 Recently, ferrocene moieties with excellent redox properties have proved to be suitable for the CDT treatment strategy. 19–23 For example, Dong et al prepared a covalent organic framework (COF)-based ferrocene (Fc) and glutathione peroxidase 4 (GP × 4) inhibitor loaded nano drug RSL3@COF-Fc to enhance ˙OH-induced cellular damage by CDT.…”
Section: Introductionmentioning
confidence: 99%